ATP Luminescence-Based Motility-Invasion Assay - Suzanne M. de la Monte; Stephanie A. Lahousse; Jade Carter; Jack R. Wands (BioTechniques)
Directional motility and invasion assays are largely based on the use of Boyden chambers or Transwell™ culture inserts in which porous membranes separate seeded cells from a chemotactic factor supplied in the medium outside the chamber. The major obstacle for most currently available assays is that they lack a sensitive, easy, and reliable method of quantifying the nonmotile cell populations. Failure to account for all cells within the assay chamber prohibits the determination of percentages of migrated cells. Here we describe an ATP luminescence-based motility-invasion (ALMI) assay that circumvents this problem, enabling investigators to quantify directional cell migration or invasiveness easily. The ALMI assay is based on the detection of ATP in viable cells harvested from inert surfaces that do not generate background signals. We demonstrate how the ALMI assay can be used to assess the effects of various experimental conditions such as growth factor stimulation and ethanol exposure on cell migration. In addition, precoating the membranes with extracellular matrix molecules enabled the measurement of the cell invasion. In conclusion, the ALMI assay provides a reliable and flexible method to quantify cell motility and invasiveness using a luminescence microplate reader.